My German question : growing up in Nazi Berlin - Gay, Peter, 1923-2015 (Yale University Press, 1998)
In this truly remarkable book, a renowned historian tells of his youth as an assimilated, irreligious Jew in Nazi Germany from 1933-1939. Publisher Fact Sheet. Describes his family; the life they led; and the reasons they did not emigrate sooner. He explores his own ambivalent feelings--then and now--toward Germany and the Germans. This insightful account is a significant contribution to the history of German Jewry and to the art of autobiography.